Pengaruh Kombinasi Latihan Rentang Gerak dan Latihan Nafas Dalam terhadap Tingkat Kelelahan pada Pasien Hemodialisis - Nurdin, Nurdin; Soesanto, Edy; Wardani, Ratih Sari; Mubin, M. Fatkhul; Vranada, Aric (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Chronic renal failure is caused by kidney damage, both structural and functional so that patients experience fluid and electrolyte imbalance and accumulation of toxins (uremia) in the body and patients require hemodialysis therapy. Hemodialysis has negative impacts including physical and psychological fatigue in patients, the prevalence reaches 60-97%, if not treated will affect the patient's quality of life and can cause dialysis disequilibrium syndrome (DDS). Objective to determine the difference in fatigue levels before and after a combination of range of motion exercises and deep breathing exercises in hemodialysis patients. Quasi experimental pretest-posttest with control group design. A sample of 58 respondents was divided into 2 groups, namely the control group and the intervention group, each consisting of 29 respondents selected using total sampling techniques based on inclusion and exclusion criteria. The control group (education and relaxation) and the intervention group (a combination of range of motion exercises and deep breathing exercises) were given pre- and post-tests and examination of urea and creatinine levels before and after. The intervention group received treatment for 6 times undergoing hemodialysis with a duration of 15 minutes. The level of fatigue was measured using the validated FACIT (Functional Assessment of Chronic Illness Therapy) - Fatigue Scale questionnaire instrument. Data were analyzed using the paired t-test and Wilcoxon signed ranks test. There is a significant difference in the level of fatigue before and after between standard therapy (education and relaxation) and the combined intervention of range of motion exercises and deep breathing exercises in hemodialysis patients. The average fatigue level was 1.2759 and 10.9334 with a standard deviation of 2.4334 and 3.9334 and obtained p-value = 0.000. The average urea level was 100.9452 and 121.7069 with a standard deviation of 33.3534 and 65.5346 and obtained p-value = 0.008, while the average creatinine level was 6.8897 and 4.6621 and a standard deviation of 3.5400 and 1.5644 and obtained p-value = 0.004 in hemodialysis patients. There was a significant difference in the level of fatigue before and after between the combination of range of motion exercises and deep breathing exercises in hemodialysis patients.  Keywords: Chronic Kidney Failure, Hemodialysis, Range of Motion, Deep Breathing, and Fatigue.  ABSTRAK Gagal ginjal kronik disebabkan oleh kerusakan ginjal, baik struktural maupun fungsional sehingga pasien mengalami gangguan keseimbangan cairan, elektrolit dan menumpuknya racun (uremia) dalam tubuh dan pasien memerlukan terapi hemodialisis. Hemodialisis memiliki dampak negatif antara lain kelelahan fisik dan psikologis pada pasien, prevalensinya mencapai 60-97%, jika tidak diatasi akan mempengaruhi kualitas hidup pasien dan bisa menyebabkan dialysis disequilibrium syndrome (DDS). Tujuan untuk mengetahui perbedaan tingkat kelelahan sebelum dan sesudah kombinasi latihan rentang gerak dan latihan napas dalam pada pasien hemodialisis. Quasy experimental  pretest-posttest with control group design. Sampel  58 responden yang dibagi menjadi 2 yaitu kelompok kontrol dan kelompok intervensi, masing-masing terdiri dari 29 responden yang dipilih menggunakan teknik total sampling berdasarkan kriteria inklusi dan eksklusi. Kelompok kontrol (edukasi dan relaksasi) dan kelompok intervensi (kombinasi latihan rentang gerak dan latihan nafas dalam) dilakukan pre dan post test serta pemeriksaan kadar ureum dan kreatinin sebelum dan sesudahnya. Kelompok intevensi memperoleh perlakuan selama 6 kali menjalani hemodialisis dengan durasi 15 menit. Tingkat kelelahan diukur menggunakan instrumen kuesioner FACIT (Functional Assessment of Chronic Illness Therapy) - Fatigue Scale yang telah tervalidasi. Data dianalisis menggunakan uji paired t-test dan Wilcoxon signed ranks test. Ada perbedaan signifikan tingkat kelelahan sebelun dan sesudah antara terapi standar (edukasi dan relaksasi)  dengan intervensi kombinasi latihan rentang gerak dan latihan nafas dalam pada pasien hemodialisis. Tingakat kelelahan rata-rata 1,2759 dan 10,9334 dengan standar deviasi 2,4334 dan 3,9334 dan diperoleh p-value=0.000. Kadar ureum rata-rata 100,9452 dan 121,7069 dengan standar deviasi 33,3534 dan 65,5346 dan diperoleh p-value=0.008, sedangkan   kadar kreatinin rata-rata 6,8897 dan 4,6621 dan standar deviasi 3,5400 dan 1,5644 dan diperoleh p-value=0.004 pada pasien hemodialisis. Ada perbedaan signifikan tingkat kelelahan sebelum dan sesudah antara  kombinasi latihan rentang gerak dan latihan napas dalam pada pasien hemodialisis. Kata Kunci: Gagal Ginjal Kronis, Hemodialisis, Rentang Gerak, Nafas Dalam, dan Kelelahan.